GANGGUAN MEMORI EPISODIK PADA EPILEPSI LOBUS TEMPORAL DAN NONTEMPORAL - Koestoer, Clara Krishanti; Bintoro, Aris Catur; Pudjonarko, Dwi (Majalah Kedokteran Neurosains Perhimpunan Dokter Spesialis Saraf Indonesia, 2018)
EPISODIC MEMORY DISORDER IN TEMPORAL AND NONTEMPORAL LOBE EPILEPSYABSTRACTIntroduction: Memory is the most defected cognitive function in neurological problems including epilepsy. Amnesia, refers to episodic memory impairment (EMI), which components are regulated by various areas related to brain lobes especially the temporal lobe. EMI represents a major cognitive component in temporal lobe epilepsy (TLE) but also encounter in focal epilepsy outside the temporal lobe.Aim: To prove the difference between EMI that occurs in TLE and nontemporal lobe epilepsy (NTLE) patients.Method: A cross-sectional study on epilepsy patients in Neurology Clinic of dr. Kariadi Hospital, Semarang from November 2016 until January 2017. Subjects were devided into TLE and NTLE group based on clinical semiology and electroencephalography (EEG). Interviews and questionnaires were done to the characteristics of subjects which can aggravate EMI, and memory tests was performed using Word List Memory Task, Word List Memory Recall, and Word List Memory Recognition. Statistical analysis using Chi-square test and multivariate logistic regression.Results: Subjects obtained were 43 respondents consisting of 21 TLE and 22 NTLE subjects. Significant difference of EMI occurrence was shown in TLE compared to NTLE, especially on delayed recall component. Patients with history of epilepsy >10 years tend to have a significant EMI, while patients with first seizure >10 years old do not tend to have EMI with or without other confounding factors.Discussion: There are differences in the occurrence of EMI on the TLE and NTLE independently, especially delayed recall.Keywords: Episodic memory impairment, temporal lobe epilepsyABSTRAKPendahuluan: Memori merupakan fungsi kognitif yang paling rentan terkena gangguan neurologis termasuk epilepsi. Salah satunya adalah amnesia, merujuk pada gangguan memori episodik (GME) yang komponennya diatur oleh berbagai area terkait lobus otak terutama lobus temporal. Gangguan memori episodik (GME) mewakili komponen kognitif utama pada epilepsi lobus temporal (ELT), namun juga tidak jarang ditemui pada epilepsi fokal di luar lobus temporal.Tujuan: Mengetahui perbedaan GME pada penderita epilepsi lobus temporal dengan epilepsi lobus nontemporal (ELNT).Metode: Penelitian potong lintang terhadap pasien epilepsi yang berobat ke Poli Saraf RSUP dr. Kariadi, Semarang pada bulan November 2016 hingga Januari 2017. Subjek dikelompokkan menjadi ENT dan ELNT berdasarkan gambaran semiologi klinis dan elektroensefalografi (EEG). Dilakukan wawancara dan pemakaian kuesioner terhadap karakteristik subjek yang dapat memperberat GME, serta tes memori menggunakan Word List Memory Task, Word List Memory Recall, dan Word List Memory Recognition. Analisis statistik menggunakan uji Chi-square dan uji multivariat dengan regresi logistik.Hasil: Didapatkan 43 subjek yang terdiri dari 21 subjek ELT dan 22 subjek ELNT. Didapatkan subjek yang mengalami GME pada ELT lebih banyak secara bermakna dibandingkan ELNT, terutama pada komponen delayed recall. Subjek yang menderita epilepsi >10 tahun cenderung mengalami GME secara bermakna, sedangkan subjek yang mengalami serangan awal pada usia >10 tahun lebih cenderung tidak mengalami GME, baik secara independen maupun bersama-sama dengan faktor perancu yang lain.Diskusi: Terdapat perbedaan terhadap terjadinya GME pada ELT dan ELNT secara independen, terutama pada komponen delayed recall.Kata kunci: Epilepsi lobus temporal, gangguan memori episodik